Exploring the unemployment crisis among speech therapists and audiologists in South Africa: perspectives on institutional roles, professional bodies, and the path to job creation - Nomfundo Moroe; Nothando Nkosi; Ben Sebothoma (BMC Health Services Research)
Abstract Background Despite the critical need for speech therapists and audiologists to meet various healthcare demands, including those outlined in the National Health Insurance Bill, unemployment among these professionals in South Africa remains a growing concern. Previous studies indicate that 16% of newly graduated speech therapists and audiologists are unemployed within the first year after completing community service, with this figure increasing to 19% by the second year. However, little is known about the lived experiences of unemployment among these professionals. Purpose To explore the lived experiences of unemployed speech therapists and audiologists after community service, including their perceptions of job creation efforts by the government, universities, and professional bodies and their reflections on their chosen field of study and considerations of alternative career paths. Methods A non-probability purposive sampling strategy was employed to recruit participants who met the inclusion criteria. Participants consisted of speech therapists and audiologists who were either currently unemployed or had experienced unemployment within the last five years. Semi-structured interviews were conducted online to collect qualitative data. Data were analysed qualitatively, following Braun and Clarke’s thematic analysis. Results Three key subthemes emerged from the data on the lived experiences of participants: (1) social and lifestyle changes, (2) mental health concerns, and (3) financial strain. Participants also shared their perspectives on job creation, emphasizing the need for universities to better prepare graduates for the private sector and for professional boards and heads of departments to advocate more effectively for the profession. Despite their challenges, participants expressed a strong commitment to their profession, with many seeking alternative roles within the field and expressing no regrets about their career choices. Discussion The findings reveal the multifaceted challenges faced by unemployed speech therapists and audiologists in South Africa, spanning systemic, social, financial, and psychological domains. Participants' experiences highlight the importance of coordinated efforts by the government, universities, professional bodies, and the private sector to address unemployment and create sustainable career pathways. Conclusion This study highlights the urgent need for systemic interventions to support unemployed speech therapists and audiologists. Efforts must focus on enhancing graduate employability, promoting advocacy for job creation, and developing alternative opportunities within the profession. Addressing these issues is essential for aligning the workforce with the nation’s healthcare needs and ensuring that speech therapists and audiologists can contribute effectively to the healthcare system.